HAMBATAN EPISTEMOLOGI SISWA DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINIER TIGA VARIABEL - Novita Indriyani; Rizki Wahyu Yunian Putra; Siska Andriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe students’ epistemological obstacles in solving problems related to systems of linear equations in three variables. This is a qualitative study conducted at MA Negeri 02 Tulang Bawang Barat involving 27 tenth-grade students, with three students selected as research subjects representing high, sedang, and low levels of mathematical problem-solving ability. The triangulation used in this research includes both source and technique triangulation. Data collection techniques consisted of tests, interviews, and documentation. Interview sources included both students and teachers. The results show that most students experienced various obstacles, including difficulties in understanding the symbolic meaning of variables, errors in applying the substitution and elimination methods, and limitations in interpreting solution results. These obstacles generally stem from an incomplete understanding of basic algebraic concepts and the interrelationships between equations in the system. These findings have important implications for the development of instructional strategies that emphasize strengthening conceptual understanding and students' mathematical thinking processes.